Evidence for Thermal‐Based Transition in Super‐Lattice Phase Change Memory. Issue 4 (18th March 2019) - Boniardi, Mattia; Boschker, Jos E.; Momand, Jamo; Kooi, Bart J.; Redaelli, Andrea; Calarco, Raffaella
Abstract : Phase change memory (PCM) device physics comprehension represents an important chapter of future development of the PCM‐based architectures and their placement into the storage class memory (SCM) segment of the memory hierarchy. Here, a reduction of SET and RESET currents by more than 60% with respect to conventional GeTe–Sb2 Te3 (GST) alloys is demonstrated by using phase change memory cells containing (GeTe–Sb2 Te3 )/Sb2 Te3 super‐lattices (SL). Further, it is demonstrated that our SL PCM devices have similar characteristics in terms of the memory transition as conventional memory cells based on GST, even though showing reduced power consumption, indicative of an efficiency augmented SET‐to‐RESET transition. The reduced power consumption may be attributed to an increased thermal resistance of the SL with respect to the bulk GST alloy. This demonstrates that it is possible to engineer PCM with enhanced performance by employing SL structures, enlarging the possibility of employing SL as SCM players. Abstract : A 60% reduction of currents in phase change memory (PCM) with super‐lattice (SL) active stacks is reported with respect to bulk stacks. Similarities between the electrical properties of SL and bulk PCM are pointed out in terms of programming curves and SET behavior, paving the way for a thermal‐based working principle in SL PCM as in the bulk counterpart.